Endovascular Versus Open Abdominal Aortic Aneurysm: Best Decision - Déglise, Sébastien; Delay, Charline; Saucy, François; Lejay, Anne; Dubuis, Céline; Briner, Lukas; Chakfe, Nabil; Corpataux, Jean-Marc (Current Pharmaceutical Design, 2015)
Since the first implantation of an endograft in 1991, endovascular aneurysm repair (EVAR) rapidly gained recognition. Historical trials showed lower early mortality rates but these results were not maintained beyond 4 years. Despite newer-generation devices, higher rates of reintervention are associated with EVAR during follow-up. Therefore, the best therapeutic decision relies on many parameters that the physician has to take in consideration. Patient’s preferences and characteristics are important, especially age and life expectancy besides health status. Aneurysmal anatomical conditions remain probably the most predictive factor that should be carefully evaluated to offer the best treatment. Unfavorable anatomy has been observed to be associated with more complications especially endoleak, leading to more re-interventions and higher risk of late mortality. Nevertheless, technological advances have made surgeons move forward beyond the set barriers. Thus, more endografts are implanted outside the instructions for use despite excellent results after open repair especially in low-risk patients. When debating about AAA repair, some other crucial points should be analysed. It has been shown that strict surveillance is mandatory after EVAR to offer durable results and prevent late rupture. Such program is associated with additional costs and with increased risk of radiation. Moreover, a risk of loss of renal function exists when repetitive imaging and secondary procedures are required. The aim of this article is to review the data associated with abdominal aortic aneurysm and its treatment in order to establish selection criteria to decide between open or endovascular repair.
Keywords: open repair